Facade, RPL House - Ghosh, Ayan (2023)
RPL House on Walchand Hirachand Marg was earlier called Shahibagh House, named after the Shahibagh Palace in Ahmedabad. The building is made of Malad stone with an arcade of semi-circular arches on the ground floor. Upper-level windows have extended overhangs. Its facade was restored by conservation architect Vikas Dilawari in 2000.